Makanan Dan Gizi Dalam Perspektif Islam Dan Kesehatan: Analisa Kajian Literatur - Wiwik Widiyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Islam is present on earth by truly caring for the human soul and mind by providing healthy food from pre-conception to the next stages of life. Food consumed by humans must contain various kinds of nutritional content that can support human life processes. This research uses a literature review method where the researcher carries out a series of research involving various kinds of information originating from literature such as books, encyclopedias, documents, and so on with the aim of finding various kinds of theories and ideas which can then formulate results in accordance with the research objectives. The results of research from various literary sources show that in Islamic teachings, food and drink consumed by humans, especially Muslims, must be selective, namely halal according to Allah's instructions in the Koran and the explanation of the Prophet Muhammad SAW in the hadith, and of thayyiban quality, namely food that is useful for the body, it is not damaging, not disgusting, delicious, does not expire and does not conflict with God's commands, because it is not forbidden. Islam and health basically have the same goal for the good of humans. Therefore, when consuming food, there are several conditions that must be met and strictly observed so that humans avoid various types of diseases that originate from food.